Persepsi dan Peran Suami dalam Pencegahan Kekurangan Energi Kronis pada Ibu Hamil di Bukittinggi - Diana Putri (JURNAL RISET RUMPUN ILMU KESEHATAN, 2024)
Chronic Energy Deficiency (CED) in pregnant women is a major nutritional challenge in Indonesia, including in Bukittinggi. Despite proper health service utilization, the burden of CED is relatively high and has a non-economic component that includes cultural and family social support.  The influence of the husband on the nutritional status of pregnant women is frequently overlooked by prevention and control strategies. This study sought to investigate husbands' thoughts and roles in the prevention of  CED  in pregnant women in  Bukittinggi.  The present study employed a qualitative phenomenological research design including 15 husbands of pregnant women (experienced and non-experienced  CED)  and  5–7  triangulation informants  (pregnant women and health workers).  Semi-structured interviews and non-participatory observations provided the data, while  NVivo  12  was employed for thematic analysis. Source triangulation and member checking validate the data. The results indicate that the majority of husbands do not understand CED scientifically and view their support solely as financial assistance. Although emotional and informational motivations can affect positive nutritional behaviors, they are still regarded as weaknesses. Among the external barriers are costs, long hours of work, and a patriarchal culture that severely restricts husbands' ability to be involved in their wives' nutritional problems. However, some informants have indicated a value shift that prioritizes emotional involvement over intellectual focus.  The  intervention strategies for future implementation should be family-based with a primary focus on couples' nutrition education, emotional  strengthening,  and  the  inclusion  of  males  in  maternal  health  programs  (e.g.,  paternity-readiness sessions